Legal Force of Auction Minutes Using Deed of Command Against Credit Guarantees at PT BPR LSE Manggala Batam Which Is Controlled by a Third Party - Angraini, Rina; Shallman, Shallman (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2026)
This study aims to determine and analyze the legal force of auction minutes using a deed of command against credit guarantees at PT BPR LSE Manggala Batam which are controlled by third parties and to determine and analyzeThe obstacles and constraints faced by PT BPR LSE Manggala in implementing auctions using deed of command against credit collateral controlled by third parties and to find out examples of deed of command. The research method used in this thesis is an empirical approach method. The specifications of this research use descriptive. The type of data used in this study is primary data which includes Law Number 5 of 1960, Law Number 4 of 1996, Law Number 10 of 1998, Law Number 2 of 2014, Civil Code, Regulation of the Minister of Finance of the Republic of Indonesia Number 122 of 2023, Regulation of the Minister of Finance of the Republic of Indonesia Number 86 of 2024 and related regulations regarding auctions and banking collateral.and secondary data consisting of books and other supporting documents. Research data collection using interview techniques and document or library material studies.The data analysis method used in analyzing the data is qualitative analysis. The results of the study can be formulated that there are stages in the process of resolving problematic loans by PT BPR LSE Manggala until the collateral is taken over (AYDA) from a third party and the sale is carried out. The implementation of the auction is contained in the Auction Minutes which contain temporary purchases by the bank with a De Command Deed. The auction minutes and the de command deed as authentic deeds have perfect legal force for the parties involved in the auction and the actual buyer who will be appointed by the bank. Obstacles and constraints in the form of internal and external factors include costs, administrative requirements, third parties who do not want to vacate the collateral, debtors who delay the execution time and the uncertain time period for each administration process while the collateral must be sold within 1 (one) year if it passes then the bank is declared the actual buyer.